PERAN SOSIALISASI POLITIK TERHADAP TINGKAT PARTISIPASI PEMILIH PEMULA PADA PILKADA 2019 DI KECAMATAN MEGANG SAKTI KABUPATEN MUSI RAWAS - Agus Tiansah (PRAJA: Jurnal Ilmiah Pemerintahan, 2023)
Political socialization is one of the urgent pillars in the implementation of a democratic party, as well as having an influence on the level of voter participation in an election, in this case the regional head election. On this basis, the researcher is motivated to prove that political socialization has an important role in increasing the participation of first-time voters in the 2019 regional head elections in Megang Sakti District, Musi Rawas Regency. In this study, the researcher used descriptive qualitative research by describing and interpreting data and facts obtained during field research from 30 informants so that in the end a hypothesis could be formulated. The results of the study show that the socialization of politics has an influence on increasing the political participation of first-time voters in Megang Sakti District, Musi Rawas Regency in the 2019 regional elections. The factors that influence the increase in the political participation of young voters are due to the influence of information and understanding of the democratic process or general elections, especially in the 2019 regional election elections.